An audiovisual representation of a geomagnetic excursion for public engagement - Schanner, Maximilian Arthus; Nielsen, Klaus; Bickerton, Peter; Panovska, Sanja; Kervalishvili, Guram (Frontiers in Earth Science, 2026)
This methodological communication paper details the creation and public reception of an audiovisual representation of the last geomagnetic excursion. Utilizing a global model of the Earth’s magnetic field, we developed a visualization and sonification designed to engage a broad audience with this extreme event in Earth’s history. The work reached over one million people online and sparked positive engagement, demonstrating the power of artistic interpretation in communicating complex scientific concepts. This project highlights the potential of innovative media formats for public outreach and science communication in the Earth sciences.